Experimental investigation of collapse in eolian soil: a case study in Mayapo, Colombia (2021)
The principal target of this research is to focus on the study of the volumetric behavior of the eolian soil and the influence of the geology, the soil structure, and suction on possible collapse behaviour of the eolian soils. An experimental program of laboratory tests was designed including geotechnical classification tests, Micro-structure tests, suction measurement, and oedometer tests included classical and unsaturated in order to know the characteristics and properties of the eolian soils. There are large and continuous macropores between grains and a low amount of micropores. The macropores could control the volumetric behaviour of the eolian soils. The salt concentration influences the osmotic suction and the total suction of the eolian soil, affecting its hydraulic condition. It can govern the water flow and attract more water to the soil, increasing the saturation degree, causing a decrease in total suction in the soil. The collapse potential of the eolian soils was classified as a moderated problem. The collapse potential increase with the increment of the initial void ratio. As suction decreases and soil wets, water menisci between liquid and vapour phase disappears, and the empty pores are flooded, and it causes a loss in the soil stiffness. The unsaturated oedometer tests allowed to understand the influence of suction on the volumetric behaviour of the eolian soils. A constitutive model was proposed to describe the volumetric behaviour of the eolian soil. The model is represented by a Loading Collapse (LC) curve, and to allow knowing the reversible compressive volumetric strains for any stress path of loading (L), collapse (C), or both in the elastic domain and to predict irreversible compressive volumetric strain for any stress loading or collapse paths. There is an important dependence of collapse and loading paths in the volumetric behaviour of the eolian soils. The deformations are very small at suction changes. The soils will suffer higher deformations in loading paths at low suction levels due to the soil stiffness is less.